Geriatric nutritional risk index predicts prognosis in hepatocellular carcinoma after hepatectomy: a propensity score matching analysis - Kanno, Hiroki (Sci Rep, 2021)
The geriatric nutritional risk index (GNRI) is widely used for nutritional assessment in older inpatients and is associated with postoperative complications and cancer prognosis. We investigated the use of GNRI to predict long-term outcomes in hepatocellular carcinoma of all etiologies after hepatectomy. Overall, 346 patients were examined after propensity score matching. We dichotomized the GNRI score into high GNRI (> 98: N = 173) and low GNRI (≤ 98: N = 173) and evaluated recurrence-free survival (RFS) and overall survival (OS) between both groups. Clinicopathological characteristics between the low- and high-GNRI groups were similar after propensity score matching except for the components of the GNRI score (body mass index and serum albumin level), Child–Pugh score (comprising serum albumin level), and preoperative alpha-fetoprotein level (p < 0.0001, p < 0.0001, p = 0.0030, and p = 0.0007, respectively). High GNRI was associated with significantly better RFS and OS (p = 0.0003 and p = 0.0211, respectively; log-rank test). Multivariate analysis revealed that GNRI is an independent prognostic factor of RFS and OS (low vs. high; hazard ratio [HR], 1.8284; 95% confidence interval [CI] 1.3598–2.4586; p < 0.0001, and HR, 1.5452; 95% CI 1.0345–2.3079; p = 0.0335, respectively). GNRI is an objective, inexpensive, and easily calculated assessment tool for nutritional status and can predict prognosis of hepatocellular carcinoma after hepatectomy.